A macro-environment approach to civil aviation strategic planning - Itani, Nadine; O'Connell, John Francis; Mason, Keith (Elsevier, 2014)
Air transport is considered a cyclical industry sensitive to the macro-environment in which it operates. As aviation policy makers and regulators strategically plan for their future, they need to consider the systematic and synergistic effects of common factors which comprise the operating environment of the industry׳s organisations. Thus, during the process of aviation systems planning governments should perceive the generic conditions which exist in the economy as a whole as equally important to air transport exclusive conditions. This paper highlights the significant impact of the national macro-environment factors on a country׳s air transport sector and it suggests including these elements within the context of civil aviation strategic planning. Country level data is collected on seventeen input variables versus four output variables on a sample of 52 countries. Structural Equation Modelling (SEM) is used to identify the descriptors with significant impact on air transport output, namely: passenger traffic, aviation total contribution to GDP, aviation total contribution to employment and air connectivity levels. The identified significant drivers are found to create an enabling environment that determines the capacity of an economy and society to benefit from the air transport system׳s productivity. The results call upon aviation policy makers and regulators to assess the national macro-environment forces during the situation analysis part of the strategic planning process. The identified operating environment conditions act as a framework for providing clear policy orientations and for facilitating the identification of areas where policy intervention could improve air transport sector׳s performance. A well-defined aviation strategy allows aviation policy makers to identify and address nation wide strategic issues and provides aviation industry׳s stake holders with guidelines to help maintain and enhance their competitive position in both domestic and global markets.
Keywords: Macro-environment; SEM; Civil aviation